A conceptual framework of the relationship between organizational resources, capabilities, systems, competitive advantage and performance - Raduan Che Rose; Jegak Uli; Haslinda Abdullah; Alimin Ismadi Ismail (2009)
Achieving a competitive advantage position relative to its business rival is what organization in particular should be aiming for. Despite the importance of attaining competitive advantage in organizations, there has been limited study on the relationship between organizational resources and the way firms are organized to achieve competitive advantage. The resource-based view (RBV) research presently has been focusing more on the attributes and characteristics of resources to build competitive advantage. This has created a gap in the body of knowledge and between the theoretical and practical aspect of managing organizations that is from the perspective of the RBV of the firm. Examining organizational competitive advantage from the resource-based view allows the organization to gauge the magnitude of importance placed upon its internal firm resources, capabilities and systems in their relationship with competitive advantage and performance.